KONDISI LINGKUNGAN PEMUKIMAN YANG TIDAK SEHAT BERISIKO TERHADAP KEJADIAN LEPTOSPIROSIS (STUDIKASUS DI KOTA SEMARANG) - Ramadhani, Tri; Yunianto, Bambang (Badan Penelitian dan Pengembangan Kesehatan, 2010)
Leptospirosis is an acute febrile illness infecting human and animal (zoonotic) and caused by the bacteria leptospira. Semarang city is one endemic leptospirosis with incidence rate in 2009 of 13,27/100.000 and case fatality rate 3,5%. The research objective was to find out the impact of settlement environment conditional with leptospirosis cases. The study was observational with cross sectional design. Population are the people who visit the health center in Semarang city and sample is a part patient in health center with clinical sympthoms leptosirosis from May up to November 2009. Leptospirosis case maintained with laboratory test uses leptotek lateral flow. Data collection with interview and obsen'ation, analyzing by univariat, bivariat (chi square) and multivariate with regresi logistic metode. Out of 105 responden, 67 (63,8%) leptospirosis positive and 38 (36,2%) negative. Poor housing had a 3,4-fold increase for leptospirosis (OR=3.4; 95% CI=1.050-10.779). Sanitary-conditional to indoor and outdoor is not significant with leptospirosis (p=0,051). Rat eksistensi in house had a 6.4-ford increase for leptospirosis (OR=6.4; 95% CI=2.081-19.983) and there is dominant factor that affect leptospirosis. Poor environmental of settlement increases risk for leptospirosis Key words, environmental, settlement, leptospirosis